Glosa (aprobująca z uwagami) do orzeczenia Sądu Apelacyjnego w Poznaniu z dnia 12 grudnia 2022 r. I ACa 525/21 - Sokołowski, Marcin (PRAWO i WIĘŹ, 2025)
Despite the fact that there is no legal regulation dedicated to trust agreements in the Polish Civil Code, this type of contract is used quite often in practice. It's necessary to solve problems when the need for interpretation arises in the case when parts of this contract are not complete. As in this text, the issue was the possibility of setting up such a trust when one part of the contract wanted the other part to acquire immovable property (an apartment) and return it to the first part after a certain period of time, which was not precisely defined. The Polish courts rejected the case on the basis of the rules of interpretation of human will's acts delivered in the Polish Civil Codex (Kodeks Cywilny), stating that there is no such possibility to use legal allegation, especially if there is no indication of any time to dissolve the contract, written in this contract between parties.